Transforming Inventory Management at RS Siloam Jantung Diagram: A Lean Driven Approach to Reducing DOI and Strengthening Patient Safety - Mariska Ajeng Andaka; Gatot Yudoko; Muhammad Hanafi (Eduvest - Journal of Universal Studies, 2026)
This research examined inventory management challenges at RS Siloam Jantung Diagram and proposed improvement initiatives to enhance operational efficiency while maintaining patient safety. As a specialized cardiovascular hospital, the availability of medical supplies is critical to ensuring uninterrupted patient care and supporting clinical outcomes. The hospital experienced persistent inventory inefficiencies, reflected in Days of Inventory (DOI) levels that consistently exceeded the organizational target of 23 days and reached a peak of 55 days. These conditions resulted in excess inventory, expired consumables, emergency procurement, redundant activities, and delayed operational decision-making, thereby increasing operational costs while posing risks to service reliability and patient safety. A mixed-method approach was employed, combining quantitative analysis of inventory performance data with qualitative insights obtained through focus group discussions, direct observations, and a 5S assessment across key operational units. The Current Reality Tree analysis identified relationships among operational issues and revealed four primary root causes: the absence of an integrated inventory management system, lack of clear ownership, unclear roles and accountability, and reliance on manual processes. These factors reduced inventory visibility, weakened cross-functional coordination, and limited timely decision-making. Based on these findings, the study proposed improvements in governance, process standardization, forecasting practices, role clarification through RACI alignment, real-time monitoring, and preparation for Warehouse Management System and hospital information system integration. The research demonstrated that addressing systemic causes rather than isolated symptoms could improve inventory performance while strengthening patient safety. The proposed framework provides a practical reference for healthcare organizations seeking sustainable inventory management practices and operational excellence.